Heart rate variability as a marker of autonomic dysfunction in children with primary Raynaud’s phenomenon - Ulusoy, Samet; Akgün, Gökmen; Bayrak, Yunus Emre; Başar, Eviç Zeynep; Sönmez, Hafize Emine; Şahin, Nihal (The Turkish Journal of Pediatrics, 2025)
Background. Primary Raynaud’s phenomenon (RP) is a functional vasospastic disorder triggered by cold or emotional stress, often occurring without an underlying systemic disease. As autonomic dysfunction is thought to contribute to RP pathogenesis, heart rate variability (HRV) analysis may provide insights into underlying mechanisms. This study aimed to assess autonomic nervous system activity in children with primary RP using HRV parameters. Methods. The study included 36 primary RP patients (0–18 years) and age- and gender-matched 30 healthy controls with normal 24-hour Holter electrocardiograms (ECG). Data on demographics, laboratory results, 24-hour Holter ECG, capillaroscopy, and treatment were collected. HRV was analyzed in both the time and frequency domains. Results. In the patient group, 11 (30.4%) were male, and 25 (69.6%) were female, with a median age of 15 (8–18) years. Symptom onset occurred at a median age of 14. The attack patterns were biphasic in 36.1% of patients, triphasic in 30.6%, and monophasic in 33.3%. Capillaroscopy was normal in 16 (44.4%) patients, with minor changes in 20 (55.6%). Six (16.6%) patients had positive antinuclear antibody (ANA) with no autoimmune disease diagnoses. Holter ECG monitoring results were compared with those of healthy controls (median age 15 years), showing significant differences in standard deviation of all normal-to-normal intervals (SDNN) and standard deviation of successive differences between adjacent RR intervals (SDSD) between primary RP patients and controls, but no differences in root mean square of successive differences (RMSSD) or HRV index values. Conclusion. Pediatric patients with primary RP showed significant autonomic changes compared to controls, though it remains unclear if these changes favor sympathetic or parasympathetic pathways. Further multicenter, prospective studies are needed to clarify these findings.